PENGARUH SALES GROWTH, PROFITABILITAS, DAN CAPITAL INTENSITY TERHADAP AGRESIVITAS PAJAK DENGAN KEPEMILIKAN INSTITUSIONAL SEBAGAI VARIABEL MODERASI (Studi Empiris pada Perusahaan Sektor Consumer Non Cyclicals yang Terdaftar di Bursa Efek Indonesia Tahun 2020-2023) - Noveirina, Ditta; Anisma, Yuneita; Safitri, Devi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2025)
This study aims to examine the influence of sales growth, profitability, andcapital intensity on tax aggressiveness with institutional ownership as moderatingvariable in non cyclicals consumer sector companies listed on the indonesian stockexchange (idx) in 2020-2023 period. The method used in this research is multiplelinear regression analysis method and moderated regression analysis with usingSPSS version 25 software. The sample selection in this study was using thepurposive sampling method. The sample in this study amounted to 208 companies.The results of this study indicate that the sales growth has no influence on taxaggressiveness, the probability and capital intensity had an influence on taxaggressiveness, the institutional ownership is not able to moderate sales growth,the institutional ownership is able to moderate the probability and capital intensityon tax aggressiveness.Keywords: Sales Growth, Profitability, Capital Intensity, Tax Aggressiveness, andInstitutional Ownership.